Recrystallization Mediates the Gelation of Amorphous Drugs: The Case of Acemetacin - Manlin Teng; Jianfeng Li; Zhaohua Li; Guangshuai Zhang; Peixu Zhao; Qiang Fu (MDPI AG, 2023)
Amorphization is widely used as an effective method of increasing the solubility of insoluble drugs. However, some amorphous drugs exhibit a much lower dissolution rate than their corresponding crystalline form due to their gelation. In this study, we reported the gels formed from amorphous acemetacin (ACM) for the first time. Gelation was promoted at conditions of lower pH, higher temperature and lower ionic strength. Solid-state characterizations suggested that ACM gels may be formed by recrystallization. This mechanism provides a new direction in facilitating the elimination of gelation for amorphous drugs. Moreover, it also provides the basis for the development of sustained-release formulations using the gelation properties.